Regional and seasonal variations of the Twomey indirect effect as observed by the ATSR-2 satellite instrument - Bulgin, C; Palmer, P; Thomas, G; Arnold, C; Campmany, E; Carboni, E; Grainger, R; Poulsen, C; Siddans, R; Lawrence, B (2008)
We use satellite observations of aerosol optical depth τa and cloud effective radius re from the ATSR-2 instrument in 1997 to investigate the Twomey indirect effect (IE, -∂ 1n re/∂ 1n τa ) in regions of continental outflow. We generally find a negative correlation between τa and re, with the strongest inverse relationships downwind of Africa. North American and eastern Asian continental outflow exhibits a strong seasonal dependence, as expected. Global values for IE range from 0.10 to 0.16, consistent with theoretical predictions. Downwind of Africa, we find that the IE is unphysically high but robust (r = -0.85) during JJA associated with high aerosol loading, and attribute this tentatively to the Twomey hypothesis accounting only for a limited number of physical properties of aerosols. Copyright 2008 by the American Geophysical Union.